A country in which I have long had a close interest : New Zealand's relations with Japan in the 1950s : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Duke, Andrew (Massey University, 2004)
This thesis examines New Zealand's relations with Japan during the 1950s, and their development from the conditions of war, to a state of relative normalcy. Particular emphasis has been given to developments in the area of trade, and the factors that influenced New Zealand's policy in the area. The wider time frame dates from about 1947, with the establishment of New Zealand's first representation in Tokyo, to New Zealand's acceptance of a full GATT trading relationship with Japan in 1962. Within this frame, the thesis is centred on two sets of trade negotiations between New Zealand and Japan. That in 1954 failed for a variety of reasons. The second, in 1958, succeeded, due to significant changes in the factors that had influenced the 1954 talks. There is a variety of secondary literature dealing with New Zealand-Japan relations in the twentieth century, and enough division of opinion and variance in argument to warrant further investigation. Tom Larkin was the first author to deal substantively with the topic, and provides an overview of post war relations to 1968, though not dealing with the specific details of the period 1954-1958. Larkin argued that there was a degree of enthusiasm on New Zealand's part to improve relations with Japan, stating there was a 'clear desire on both sides for closer ties', 1 Tom Larkin, New Zealand and Japan in the Post War World, Wellington: New Zealand Institute of International Affairs, 1969, p. 8. and that each country '...consciously sought to draw near the other...' 2 Ibid., p. 13. Larkin later commented that the period 1951-61 was marked '...most of all, by a positive decision on New Zealand's part to commit itself to the pursuit of friendly relations with Japan.' Larkin, 'The Place, Directions and Future Needs of New Zealand Relations with Japan', in New Zealand & Japan - The Papers of the Sixteenth Foreign Policy School University of Otago 1981, Dunedin: University of Otago, 1981, p. 90. Larkin suggested that fear of resurgent Japanese militarism partially determined New Zealand's attitude to the process of making peace with Japan, but that in 1951 the country was '...probably even more sensitive to the possibility of danger of from the communist world...', and the danger of Japan coming into the communist orbit. 3 Ibid., p. 6. However, after this early preoccupation with the political, Larkin argues that economic growth and trade opportunities were '...principally responsible for the transformation of relations, and the vast expansion of contacts...' 4 Ibid., p. 7. Larkin's argument was that New Zealand's motives for improving relations with Japan in the early 1950s were political, but later in the 1950s became economic. Nearly all subsequent work by other authors accepts this 'two periods' argument, albeit with chronological deviations. The idea is also referred to as determining New Zealand's external relations more generally, by two former Secretaries of Foreign Affairs, Sir George Laking, and Graham Ansell. 5 Sir George Laking, 'George Laking', in An Eye, an Ear, and a Voice, Malcolm Templeton (ed.), Wellington: Ministry of Foreign Affairs, 1993, p. 51 and Graham Ansell, 'Graham Ansell', in ibid., p. 152. The idea of two distinct 'political' and 'economic' periods, or policies, is also referred to by Keith Jackson, New Zealand Foreign Policy, paper delivered at the University of Otago Fourth Residential School on Foreign Policy, May 1969, p. 1.
"Primary source documents held with archival copy in Library"
Keywords: New Zealand; Japan; Foreign relations -- History; Foreign economic relations -- History; New Zealand, History -- 1945-1984